NuSTAR observations of Mrk 766: distinguishing reflection from absorption. Issue 3 (1st August 2018) - Buisson, D J K; Parker, M L; Kara, E; Vasudevan, R V; Lohfink, A M; Pinto, C; Fabian, A C; Ballantyne, D R; Boggs, S E; Christensen, F E; Craig, W W; Farrah, D; et al.
ABSTRACT: We present two new NuSTAR observations of the narrow-line Seyfert 1 (NLS1) galaxy Mrk 766 and give constraints on the two scenarios previously proposed to explain its spectrum and that of other NLS1s: relativistic reflection and partial covering. The NuSTAR spectra show a strong hard (>15 keV) X-ray excess, while simultaneous soft X-ray coverage of one of the observations provided by XMM–Newton constrains the ionized absorption in the source. The pure reflection model requires a black hole of high spin ( a > 0.92) viewed at a moderate inclination (i=46_-4^+1 ^° ). The pure partial covering model requires extreme parameters: the cut-off of the primary continuum is very low (22_-5^+7 keV) in one observation and the intrinsic X-ray emission must provide a large fraction (75 per cent) of the bolometric luminosity. Allowing a hybrid model with both partial covering and reflection provides more reasonable absorption parameters and relaxes the constraints on reflection parameters. The fractional variability reduces around the iron K band and at high energies including the Compton hump, suggesting that the reflected emission is less variable than the continuum.